Revised Lie Group Analysis of the Time Fractional (2+1)-Dimensional Zakharov-Kuznetsov (q, p, r) Equation - Jian-Gen Liu; Yu-Feng Zhang; Jing-Qun Wang (Fractal and Fractional)
This article presents a comprehensive study of the (2+1)-dimensional Zakharov–Kuznetsov (ZK) <semantics>(q,p,r)</semantics> equation with time fractional derivativeUtilizing the fractional Lie group method, we derive several results, including the symmetries, similarity reductions and conservation laws for this equation. Our findings not only correct previous errors in the literature but also introduce new results, such as the Lie transformation group and optimal system for this model. The study provides a rigorous mathematical framework for analyzing this fundamental model, which describes nonlinear ion-acoustic wave evolution in magnetized plasmas.